2020
DOI: 10.1093/tbm/ibaa018
|View full text |Cite
|
Sign up to set email alerts
|

Future directions for implementation science at the National Cancer Institute: Implementation Science Centers in Cancer Control

Abstract: The National Cancer Institute (NCI) Cancer Moonshot initiative seeks to accelerate cancer research for the USA. One of the scientific priorities identified by the Moonshot’s Blue Ribbon Panel (BRP) of scientific experts was the implementation of evidence-based approaches. In September 2019, the NCI launched the Implementation Science Centers in Cancer Control (ISC3 or “Centers”) initiative to advance this Moonshot priority. The vision of the ISC3 is to promote the development of research centers to build capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 22 publications
0
39
0
Order By: Relevance
“…Genomic testing of MC1R for skin cancer risk may promote behavior change across ethnically and racially diverse populations [37], especially among Hispanics, who generally have low skin cancer risk awareness [38][39][40][41][42][43]. Meta-analytic work has shown that genetic information motivates behavior change and does not generate high levels of distress or worry [44], yet the use and impact of genetic information in diverse community settings [45] is extremely understudied [46]. This randomized controlled trial ("SOMBRA: Skin Health Online for Melanoma: Better Risk Assessment") was conducted in a diverse primary care population in Albuquerque, New Mexico, which experiences year-round sun exposure [47].…”
Section: Introductionmentioning
confidence: 99%
“…Genomic testing of MC1R for skin cancer risk may promote behavior change across ethnically and racially diverse populations [37], especially among Hispanics, who generally have low skin cancer risk awareness [38][39][40][41][42][43]. Meta-analytic work has shown that genetic information motivates behavior change and does not generate high levels of distress or worry [44], yet the use and impact of genetic information in diverse community settings [45] is extremely understudied [46]. This randomized controlled trial ("SOMBRA: Skin Health Online for Melanoma: Better Risk Assessment") was conducted in a diverse primary care population in Albuquerque, New Mexico, which experiences year-round sun exposure [47].…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, the National Cancer Institute (NCI) issued requests for funding to support Implementation Science Centers for Cancer Control (ISC 3 ) (2019-2024) (9)(10)(11). Each of the seven funded ISC 3 centers conducts pilot work in IS approaches and includes an "implementation laboratory" that provides important linkages with clinical and community sites.…”
Section: Introductionmentioning
confidence: 99%
“…These include three large research networks: Accelerating Colorectal Cancer Screening and follow-up through Implementation Science (ACCSIS; https://healthcaredelivery.cancer.gov/accsis ), Improving the Management of Symptoms during and following Cancer Treatment (IMPACT; https://healthcaredelivery.cancer.gov/impact ), and most recently the Implementation Science Centers in Cancer Control (ISC3; https://cancercontrol.cancer.gov/is/initiatives/isc3 ). ISC3 includes seven Centers to support the rapid implementation of evidence-based strategies across the cancer control continuum with a focus on health equity [ 35 ]. These multipronged efforts reflect a tremendous opportunity to simultaneously advance the field of implementation science and cancer care.…”
mentioning
confidence: 99%